Equine Alpha-fetoprotein Levels in Thoroughbred Mares with Normal and Pathological Pregnancies - Kurban, İbrahim and Toydemir Karabulut, Tuğba Seval Fatma and Kiliçarslan, Mehmet Ragip (Acta Scientiae Veterinariae, 2023)
Background: Alpha-fetoprotein (AFP) is a fetal protein that was first defined in 1956 and has been used since the 1970s to identify high-risk pregnancies for abnormalities in gynecology. First description of fetal protein was by Bergstrand and Czar in 1956 in humans and named as ‘‘alpha-fetoprotein’’ (AFP). AFP was found in the electrophoresis of fetal serum (pH 8.6) and migrated from serum albumin faster than slow alpha-1-globulin, and was located in the alpha globulins region. AFP has also been used as a tumor marker in many neoplastic formations and was later shown to be present in other mammalian species. The aim of our study was to determine the concentrations of maternal serum alpha-fetoprotein (MSAFP) during pregnancy of Thoroughbred mares and to investigate the possible differences of MSAFP in normal and pathological pregnancy. Materials, Methods & Results: The horses (Equus caballus) in this study were Thorougbred mares (n = 66) permanently housed at the Karacabey Stud of the Turkish Jockey Club. The mares were subjected to regular health checks. The mares that were healthy on clinical examination, had regular cyclic activity and were bred by different stallions during the 2019 official breeding season (15 February - 30 June) were randomly selected for inclusion in the study. The mares were divided into two groups: Mares with normal pregnancies (group I, n = 42) and mares with pathological pregnancies (group II, n = 24). Group II was divided into subgroups of embryonic loss (n = 11), abortion (n = 10), preterm birth (n = 2), and premature placental abruption (n = 1). The possible relationships between mean MSAFP and foal sex, birth weight, time of birth, and IgG concentration in colostrum were also investigated. The mean MSAFP concentration was 46.78 ± 0.87 pg/mL in normal pregnancies and 70.69 ± 3.86 pg/mL in pathological pregnancies (P ≤ 0.001). No positive association was found between mean MSAFP concentration and colostrum quality or birth weight (P > 0.05). Discussion: In human medicine, alpha-fetoprotein is actively used in clinical practice as a tumour marker and as a screening test for early diagnosis of pregnancy pathologies in women. Pregnancy pathologies and embryonic losses cause great economic losses in horse breeding. Considering that the breeding season is limited, especially in thoroughbred racehorse breeding, it is important for breeders to identify mares that will experience pregnancy pathologies in the future during the breeding season. In our study, MSAFP concentrations were found to be higher than normal in mares with pregnancy pathologies such as embryonic death, abortion and premature placental separation, which is consistent with other studies. It was reported that a negative correlation was found between the age and gestational age of mares and MSAFP, but no correlation was found between the sex, birth weight, chest and leg circumference of foals and MSAFP concentration. Studies have shown that MSAFP may be a marker for pregnancy pathologies. In a study investigating the effects of seasons on MSAFP concentrations of mares, it was reported that MSAFP concentrations were higher in summer months compared to spring months (P = 0.0378) and MSAFP concentrations were higher in the last month of pregnancy compared to the previous months (P = 0.0117).These findings are supported by the results of our study. By measuring MSAFP concentrations, pathological pregnancy can be predetermined, interventions can be made and it can be possible to obtain one foal per year. Keywords: alpha-fetoprotein, thoroughbred mares, embryo loss, abortion, anomaly, foal.